KEBERTAHANAN KOSAKATA PERTANIAN DALAM BAHASA KONJO PADA SISWA KELAS 3 SMP NEGERI 31 BULUKUMBA KABUPATEN BULUKUMBA - Fitriani Basri; Wa Ode Halfian (Cakrawala Listra: Jurnal Kajian Sastra, Bahasa, dan Budaya Indonesia, 2024)
The research is aimed to describe the rate of survival of the vocabulary of agriculture in language Konjo on students grade 3 SMP Negeri 31 Bulukumba in District Bulukumba . The method that is used is the approach qualitative supported by the analysis of quantitative . The collection of data is done by using the 2 ( two ) ways , namely : questionnaire technique ( questionnaire ) and interview technique ( interview ). The results of the study have demonstrated that of the 100 vocabulary that is submitted to the 51 respondents , there is one respondent with knowledge of vocabulary highest is 91% and the knowledge of the lowest 29%. For every vocabulary knowledge on the whole respondents, survival highs are in the vocabulary of god , canggoren , workshops , asu , bembe, and rarely with the level of viability highest is 100%. While the lowest is cakkuru with a percentage of 5,88 %. So for the final results the vocabulary survival level in all questionnaires is 64,96 %. Words key : vocabulary , Konjo Languange , environment agriculture .